I Am Match with Teams: How Person-Team Fit Facilitates Team Creativity? - Xinyue Lin; Haoyang Zhang; Manna Zhang; Yan Zhang; Juan Du (SAGE Open)
As diversity becomes more widespread within teams, it is crucial to examine the dynamics of person-team fit and its effect on team creativity. By exploring the interplay between complementary fit and supplementary fit, this study aims to shed light on how these two dimensions of person-team fit contribute to the creative processes within teams based on the optimal distinctiveness theory (ODT). A two-wave field survey was conducted among 363 frontline employees within 113 teams in hotels. The regression results indicated a positive association between complementary fit and team creativity. Furthermore, the mediating role of information elaboration in this relationship was observed. Supplementary fit played a positive moderating effect between complementary fit and team creativity whereby teams with higher levels of complementary fit demonstrated higher levels of team creativity, particularly when supplementary fit was also high. Our findings thus provide significant implications for organizations seeking to enhance team creativity, that is, ensuring an inclusive climate that promotes the emergence of shared perceptions regarding both complementary and supplementary fit.